(untitled) (Journal of Engineering, 2022)
The AlAdhaim Dam is located 133 kilometers northeast of Baghdad. It is a multipurpose dam and joints the Iraqi dam system in 2000. It has a storage capacity of 1.5 billion m3. The dam has an ogee spillway with a length of 562 m, a crest level of 131.5 m.a.m.s.l. and a maximum discharge capacity of 1150 m3/s at its maximum storage height of 143 m.a.m.s.l. This research aimed to investigate the hydrodynamics performance of the spillway and the stilling basin of AlAdhiam Dam by using numerical simulation models under gated situations. It was suggested to modify the dam capacity by increasing the dam’s storage capacity by installing gates on the crest of the dam spillway. The FLUENT program was used to simulate the flow over the spillway. The free surface was calculated using the volume of fluid (VOF) method. To deal with turbulence, the SST k-ω turbulence model was used. The study showed that the spillway is capable of carrying the designed flood discharge and the modified conditions with negative pressure behind the gate and at some points along the spillway. Hydraulic jumps occur at various distances throughout the plunge pool depending on the incoming velocity in the flip bucket.